2010
DOI: 10.1111/j.1537-2995.2010.02647.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitro protection of umbilical cord blood–derived primitive hematopoietic stem progenitor cell pool by mannose‐specific lectins via antioxidant mechanisms

Abstract: The data show that both BL and GL protect the primitive HSPCs in vitro and may also serve as cost-effective HSPC enrichment tools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…These in vitro effects have been described for other lectins belonging to tarin family, the GNA-related lectins, such as those found in banana, artocarpin, garlic, and dolichos. These lectins are able to promote the maintenance of human and murine cord blood C34 + cells, in vivo and in vitro [ 11 , 12 ]. Studies have demonstrated the interaction of these lectins with stromal and CD34 + cells in a carbohydrate-dependent manner and the subsequent reduction of reactive oxygen species (ROS) level as a putative molecular mechanism for the maintenance of CD34 + cells [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…These in vitro effects have been described for other lectins belonging to tarin family, the GNA-related lectins, such as those found in banana, artocarpin, garlic, and dolichos. These lectins are able to promote the maintenance of human and murine cord blood C34 + cells, in vivo and in vitro [ 11 , 12 ]. Studies have demonstrated the interaction of these lectins with stromal and CD34 + cells in a carbohydrate-dependent manner and the subsequent reduction of reactive oxygen species (ROS) level as a putative molecular mechanism for the maintenance of CD34 + cells [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…37 Similarly, Hinge et al showed that the mannose-containing carbohydrate moieties present on the hematopoietic stem and progenitor cells were recognized by mannose-binding lectins and played an importantrole in the HSPC-protecting effect of these lectins. 38 The protective effect of mannose-binding lectins has also been demonstrated by Li et al, where the effect of a mannose-binding lectin, NTL, purified from Narcissus tazetta var. chinensis, prolonged the maintenance and expansion of cord blood CD34+ cells.…”
Section: Discussionmentioning
confidence: 74%
“…Similarly, Hinge and coworkers, showed that the mannose-containing carbohydrate moieties present on the hematopoietic stem and progenitor cells were recognized by mannose-binding lectins and played an important role in the HSPC-protecting effect of these lectins (Hinge et al, 2010). The protective effect of mannose-binding lectins has also been demonstrated by Li and coworkers where the effect of a mannose-binding lectin, NTL, purified from Narcissus tazetta var.…”
Section: Discussionmentioning
confidence: 78%